"Meko Oyasi", a Sakhalin Ainu ucaskuma narrated by Haru Fujiyama - Elia Dal Corso (De Gruyter Mouton, 2022)
In this chapter, we would like to present a folktale of the Sakhalin Ainu tradition narrated by Haru Fujiyama, who was a speaker of the Rayciska dialect of Sakhalin Ainu and also one of the last native speakers of this Ainu variety. The folktale entitled meko oyasi ‘the cat spirits’ was originally included in a corpus of West Sakhalin Ainu folklore and conversations published as Sakhalin Ainu: Materials (カラフトアイヌ語 – 資料 Karafuto Ainugo: Shiryō) (The Karafuto Ainu language – Texts) by Kyōko Murasaki in 1976.